Adsorptive defluoridation from aqueous solution using a novel blend of eggshell powder and chitosan nanofibers. (9th December 2020) - Abbasi, Aamir; Memon, Sheeraz Ahmed; Qureshi, Raja Fahad; Mehdi, Mujahid; Khatri, Muzamil; Ahmed, Farooq; Khatri, Zeeshan; Kim, Ick Soo
Abstract: Groundwater mostly contains many impurities thus can not be consumed as drinking water directly. The acceptable limit of fluoride in drinking water is 0.5–1.5 mg l −1 recommended by World Health Organization (WHO). In this research, a novel nanofiber hybrid; based on Chitosan (CTS) and Eggshell (EGG) was prepared via electrospinning technique and investigated for deflouridation from aqueous solution. SEM images reveal bead-free, smooth morphology and the FTIR confirmed the presence of chitosan and egg within the novel nanofiber blend. The defluoridation efficiency was assessed by varying the different parameters like pH, mass of nanofibers, contact time and initial concentration for adsorption. Studies revealed that CTS/EGG nanofibers hybrid shows incredible adsorption efficiency of 86%. Furthermore, isotherm studies show that the Langmuir isotherm model was well fitted for both CTS and CTS/EGG nanofibers.